PEMBUATAN SABUN DARI LIMBAH MINYAK JELANTAH SAWIT DAN EKSTRAKI DAUN SERAI DENGAN METODE SEMI PENDIDIHAN - Agus .; Didik .; Nida .; Gloria . (Program Studi Teknik Kimia, Universitas Pamulang, 2017)
Has done a solid soap-making by utilizing waste palm oil and lemongrass leaf extract. Refined palm oil waste by the addition of NaOH 15%, then added activated carbon is heated and filtered. Saponification process is done using NaOH 40% by weight ratio of palm oil and NaOH 2: 1, while the leaves of lemongrass extract, written with two variations, namely 14%, 15% and 20% by weight. Testing the quality of the soap made include testing of pH, water content, and a color test. From these results obtained in all variations addition of lemongrass leaf extracts produce soaps with a pH of 9.8 s / d 9.9, which meets the SNI standard. Testing the water content is obtained that meet SNI 06-3532-1994 is the addition of lemon grass leaf extract 14% by weight with a moisture content of 15%. While the addition of lemongrass extract 15% and 20% obtained water content exceeded that obtained SNI standard by 17% by weight and 37.7% by weight.Keywords: NaOH, palm oil, SNI